Correlation of hepatic artery resistive index with portal pressure and serum nitric oxide levels in patients with extrahepatic portal vein obstruction - Abhishek Gupta; Veereshwar Bhatnagar; Anjan Kumar Dhua; Manisha Jana; Archana Singh; Rohan Malik (Wolters Kluwer Medknow Publications, 2020)
Aim: The aim was to study the correlation of hepatic artery resistive index (HARI) with the portal pressure (PP) and its surrogate marker serum nitric oxide (NO) levels and to determine the validity of HARI as noninvasive indirect marker of PP in extrahepatic portal venous obstruction (EHPVO) pre- and postoperatively. Methods: A prospective study was conducted on 19 patients with EHPVO undergoing proximal lienorenal (LR) shunt or devascularization from February 2016 to January 2018. HARI, calculated from Doppler sonography, and NO were measured preoperatively and 14, 30 and 90 days postoperatively. Intraoperatively, PP was measured before splenectomy, and both PP and NO were measured postshunt. Results: Mean age was 10.58 ± 2.85 years, and male:female ratio was 15:4. LR shunt was done in 16 while three patients required devascularization. There was a significant fall in the HARI (0.06 ± 0.02, P = 0.02), NO (14.31 ± 2.66 μmol/l, P < 0.001), and PP (11.81 ± 1.03 mmHg, P < 0.001) following shunt surgery. However, fall in HARI did not correlate with fall in PP. Preoperative HARI also did not correlate with preshunt/devascularization PP nor with preoperative NO. Postoperatively, HARI did not correlate with NO at 14-, 30-, and 90-day follow-up. Conclusion: HARI bears no correlation with PP or NO. Hence, it cannot be used as an indirect marker of PP.